Improving Students Speaking Skills Through Role Play at Junior High School - Lisa Susanty R; Margana; Yuyun Yulia (Universitas Islam Negeri Palopo, 2026)
This classroom action research aimed to improve the English-speaking skills of ninth-grade students at SMPN 2 Dusun Selatan within the framework of Kurikulum Merdeka. The study addressed two key objectives: (1) examining how role-play enhances speaking proficiency, and (2) exploring students' perceptions of the method. Using Kemmis and McTaggart's action research model which was conducted over two cycles involving 23 students serving as the respondents of this study. Data were collected through observations and questionnaire distribution. To back up the gathered data, pre-test and 2 post-tests were conducted. The gathered data were analyzed with the utilization of quantitative and qualitative analysis. The findings demonstrate that the implementation of role-play significantly improved students' speaking performance, as evidenced by the progressive increase in test scores across pre-test, post-test cycle 1, and post-test cycle 2. Questionnaire responses indicated overwhelmingly positive perceptions, with students reporting reduced anxiety and increased confidence. Observational data further revealed enhanced communicative competence, greater spontaneity, and stronger peer collaboration. The results strongly suggest that structured role-play activities can effectively foster both linguistic and affective development in an EFL classroom setting. The study contributes to the body of knowledge by demonstrating the efficacy of sustained role-play implementation in an Indonesian EFL context, aligning with Kurikulum Merdeka's communicative objectives. It also highlights the importance of iterative practice and peer collaboration in reducing speaking anxiety, a finding that extends previous research.